Financial Strategies of Companies in the Sucroenergetic Sector - Bomfim, Fernanda Costa Neves [UNESP]; Conceicao, Elimar Veloso; Santos, David Ferreira Lopes [UNESP] (Editora Univ Estado Bahia, 2022)
This study evaluates the financial strategies adopted by companies in Brazil's sugar-energy sector and examines their impact on financial performance indicators. For this purpose, annual financial data from 70 companies including mills and distilleries from 1998 to 2018 were used. The data were obtained by combining different private databases. The regression method with panel data was used. It was found that companies oriented to Return on Investments present variables related to revenue variation, asset size, indebtedness, and financial slack as determinants. Thus, the highest level of financial performance is influenced by financial strategies based on asset growth, ability to generate new revenue, low level of indebtedness, and high financial slack associated with cash availability to meet the obligations inherent to the debt profile. These results can provide important insights for the efficient allocation of resources, the formulation of sustainable growth plans, and the debt management of companies in the sugar-energy sector.
Keywords: Investment; Capital structure; Liquidity; Profitability; Sugar-alcohol